2014
DOI: 10.1155/2014/632757
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Mastication of Utah Juniper Encroaching Sagebrush Steppe Increases Inorganic Soil N

Abstract: Juniper (Juniperusspp.) has encroached on millions of hectares of sagebrush (Artemisiaspp.) steppe. Juniper mechanical mastication increases cover of understory species but could increase resource availability and subsequently invasive plant species. We quantified the effects of juniper mastication on soil resource availability by comparing total C, total N, C : N ratio, Olsen extractable P, sulfate S, and pH using soil samples and inorganic N (NO3-+NH4+) using ion exchange membranes. We compared resource avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…In fact, only mountain big sagebrush sites treated with mastication showed consistently greater positive changes to both herbaceous components for seeded compared to unseeded sites. These results agree with previous studies reporting greater increases for mastication than cutting [ 142 ] and enhanced seedling establishment in mastication treatments where mulch deposition ameliorates seedbed temperature and increases surface soil water availability and inorganic soil nitrogen content [ 73 , 98 , 132 , 189 , 190 ]. Our results also indicated that the majority of responses for perennial grass and forb components became significant only for seeded sites, suggesting that seeding might be necessary more often than typically prescribed [ 89 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, only mountain big sagebrush sites treated with mastication showed consistently greater positive changes to both herbaceous components for seeded compared to unseeded sites. These results agree with previous studies reporting greater increases for mastication than cutting [ 142 ] and enhanced seedling establishment in mastication treatments where mulch deposition ameliorates seedbed temperature and increases surface soil water availability and inorganic soil nitrogen content [ 73 , 98 , 132 , 189 , 190 ]. Our results also indicated that the majority of responses for perennial grass and forb components became significant only for seeded sites, suggesting that seeding might be necessary more often than typically prescribed [ 89 ].…”
Section: Discussionsupporting
confidence: 92%
“…While this mechanism explains the robust changes associated with chaining in understory vegetation, including the only significant positive change in sagebrush (i.e., at mountain big sagebrush sites), it had a similar effect on annual grasses, particularly at black and mountain big sagebrush sites [ 79 , 182 , 183 , 184 ]. Mastication is also known to promote annual grass establishment, more so than perennial grasses ([ 98 , 132 , 141 , 185 , 186 , 187 ], but see [ 188 ]) because the production and distribution of mulch favors annual grass growth by reducing soil temperature, increasing soil moisture, and elevating inorganic nitrogen supply to plants [ 39 , 73 , 132 , 189 , 190 ]. These results indicate that annual grasses will likely proliferate in the short-term even when perennial grasses increase following P–J reduction [ 116 , 142 , 187 ].…”
Section: Discussionmentioning
confidence: 99%
“…These materials also consist of 168 extremely woody components (e.g., logs and large branches) generally reserved for FWD (diameter > cm; Muller-Using and Bartsch, 2009) that are only reduced in size but not 170 different in chemistry. Specifically, the diameter of FWD ranged from 0.1-7.5 cm (Young et al, 2014) and FWD was piled on top of tree-islands. 172…”
Section: Fwd Manipulation and Soil Sampling 158mentioning
confidence: 99%
“…Similar to cut and leave, materials created from mastication (wood chips) would reduce erosion and increase soil organic matter over the long term. Annual and perennial grass production would increase in areas where mastication takes place due to increased inorganic nitrogen available in the soil (Young et al 2014).…”
Section: Masticationmentioning
confidence: 99%